(untitled) (Zaporizhzhia Historical Review, 2021)
The main directions of the official correspondence of the Southern Ukraine’s customs (the period of the custom line’s beginning) are determined, the directions of the official correspondence’s components and peculiarities are considered, the directions of the official correspondence’s changes according to the improvement of the custom’s line and Southern Ukraine custom’s management.